(untitled) (Geologica Macedonica, 2015)
The Frolosh Greenstone Belt (FGB) is traced at a distance of more than 200 km in the territories of Bulgaria, Macedonia and Serbia. It consists of various greenschist-facies rocks (actinolite schists, phyllites, calcareous schists, impure marbles, metasandstones, metadiabases, massive green rocks, etc.) of the Frolosh metamorphic complex with bodies of metabasites (including lherzolites), and inliers (retrogressed mica gneisses and migmatites) from the Ograzhdenian supercomplex. The complex is intruded by bodies of gabbro (occasionally with ultramafic cumulates), diorites to granites (Struma diorite formation). U-Pb studies on zircons yielded Cadomian ages within the time span between c. 574 and 517 Ma. The Frolosh complex covers the ultrametamorphic (migmatized gneisses and amphibolites; tourmaline-biotite schists; quartzo-feldspathic gneisses; lensoid bodies of metaperidotites to norites) of the Ograzhdenian supercomplex. The Ograzhdenian rocks are intersected by diatectic metagranites overprinted by amphibolite-facies metamorphism. Dominant U-Pb ages vary between 470 and 430 Ma. The contact between the Frolosh complex and the Ograzhdenian supercomplex has been subject of long discussion and controversial interpretations. Now we emphasize on the multistage developments of both complexes as demonstrated both by field evidence and isotopic dating. The Ograzhdenian supercomplex has been subject of Precambrian tectonometamorphism witnessed by Rb-Sr whole-rock isochron data and relict U-Pb zircon data. Ordovician to Silurian anatectites (metatectic migmatization, diatexis) are intruded by Permo-Triassic granites. The contact between the Ograzhdenian supercomplex and the covering Frolosh complex is regarded as a thick complex zone of multistage tectonometamorphic development rather than a “razor-blade” surface of one-stage origin. As a boundary between suprastructure and infrastructure, it played an important role throughout the Phanerozoic, and acted as a screen with a steep thermal gradient during the Ordovician-Silurian anatexis and metamorphism in the Ograzhdenian supercomplex. For to verify this hypothesis, new detailed structural and isotopic studies are needed.